Liberalism : the classical tradition - Von Mises, Ludwig, 1881-1973 (Lib Works Ludwig Von Mises PB Ser., 2005)
"This book presents the theoretical and practical arguments for liberalism. Mises contrasts liberalism with other conceivable systems of social organization such as socialism, communism, and fascism. He is also more specific here than elsewhere in applying the liberal program to economic policy, domestic and foreign."--Jacket